Dual responsive cellulose microspheres with high solid-state fluorescence emission - Yadav, Prashant; Prajitha, K. P.; Dhaware, Vinita; Subramani, Mohan; Joy, Pattayil; Asha, S. K.; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2020)
Materials that respond to multiple stimuli such as magnetic field and light are attractive for security and medical diagnostic applications. One of the major challenges in dual functional microspheres is that the presence of magnetic nanoparticles can quench fluorescence emission. Also, there is a probability of solid-state quenching due to the proximity of the fluorophore. We report here a facile approach to prepare cellulose microspheres with high solid-state fluorescence using 40 % tetrabutylammonium hydroxide (TBAH). The fluorescence quenching effect due to the presence of Fe3O4 nanoparticles and solid-state quenching due to aggregation of fluorophore was systematically investigated. Microspheres with the detectable magnetic response and fluorescence quantum yield as high as 0.57 (FMB 414) was obtained by optimizing the reaction conditions. Such a high quantum yield has not been reported before for dual stimuli-responsive fluorescent microspheres. The magnetic and fluorescent properties were found to be durable even after multiple washing cycles. These dual responsive cellulose microspheres can be added as security features to authenticate documents such as passports, degree certificates, currency notes, financial documents etc.
Keywords: Fluorescent; Magnetic; Microcrystalline cellulose; microspheres; Stimuli responsive microspheres; Tetrabutylammonium hydroxide

Double encapsulation of liquid active compounds using nanoclay reinforced polyurea microcapsules - Aher, Yogeshwar P.; Torris, Arun; Adhikari, Benu; Shukla, Ravi; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2023)
In recent years, there has been growing interest in the double encapsulation of drugs, agrochemicals, and fragrances, aiming to achieve the highest encapsulation efficiency and preserve the activity of the encapsulated core over an extended duration. However, when active ingredients in liquid form are double encapsulated, preventing the rupture of primary microcapsules during the second encapsulation process and the leakage of the encapsulated core are major challenges. This report describes a method that utilizes polyurea and starch for successful double encapsulation of dimethyl phthalate (DMP), a liquid insect-repellent, as a model active component. We demonstrate that the incorporation of 3 wt% montmorillonite (MMT) nanoclay strengthens the polyurea wall of the primary microcapsule and prevents its rupture during double encapsulation with starch. This process facilitates the uniform distribution of polyurea microcapsules within the starch matrix and significantly improves the mechanical integrity of the nanocomposite microcapsules embedded in starch. The double-encapsulated system developed in this study significantly reduces the release rate of encapsulated DMP.
Keywords: Controlled release; Double encapsulation; Microcapsules; Microencapsulation; Nanocomposites; Starch matrix

Double-encapsulated controlled release system for the staged delivery of a growth stimulant and herbicide - Aher, Yogeshwar P.; Adhikari, Benu; Shukla, Ravi; Marimuthu, S.; Shanmuganathan, Kadhiravan (ACS Agricultural Science & Technology, 2025)
Weed control remains a critical challenge in agriculture, especially with parasitic weeds such as Orobanche spp., Striga spp., and Cuscuta spp., which significantly reduce crop yield. Although herbicides are effective against common weeds, they are less effective against parasitic weeds due to their unique germination mechanisms and close association with host plants. Growth regulators can stimulate the germination of parasitic weeds (suicidal germination) in the absence of host plants, providing a potential opportunity for controlling parasitic weeds, especially Striga sps. We report here a double-encapsulated staged delivery system, wherein herbicide (atrazine) is encapsulated in the inner polyurea shell and a growth stimulant (Gibberellic acid, GA3) in the outer alginate matrix. In vitro release study conducted in an aqueous medium showed that the time required for 50% release of atrazine from this double-encapsulated system is 96 h against 3 h for GA3. The quick release of GA3, followed by a slow and sustained release of atrazine, is expected to first induce the germination of parasitic weed seeds using GA3 and subsequently exterminate them upon exposure to atrazine. Interpretation of release data using the Weibull model led to the conclusion that the release of atrazine and GA3 is primarily governed by Fickian diffusion. Soil breakthrough profile shows that double encapsulation of atrazine helps to control the overleaching of atrazine into the soil.